2015
DOI: 10.1016/j.jphs.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin causes dedifferentiation via the extracellular signal-regulated kinase (ERK) pathway in rabbit articular chondrocytes

Abstract: Salinomycin (SAL), a monocarboxylic polyether antibiotic isolated from Streptomyces albus, modulates various cellular responses, including proliferation, apoptosis, and inflammation. However, the effect of SAL on the dedifferentiation of chondrocytes remains unclear. Thus, we investigated the effects and regulatory mechanisms of SAL on the dedifferentiation of rabbit articular chondrocytes. Our results indicate that SAL-induced a loss of type II collagen and decreased sulfated proteoglycan levels in a dose- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…TQ-induced inflammation is mediated by the phosphoinositide 3-kinase (PI3K) and p38 pathways, while PEP-1-SIRT2-induced inflammation is mediated by the p38 and ERK pathways. The authors also reported that salinomycin (SAL) causes the dedifferentiation of rabbit articular chondrocytes via the ERK pathway, as determined by increased ERK activity without alterations in JNK and p38 activity following treatment with SAL 79 . Recently, the authors revealed that PEP-1-glutaredoxin-1 increased endoplasmic reticulum-stress and then stimulated the dedifferentiation of rabbit chondrocytes via the ERK-1/2 pathway 75 .…”
Section: Introductionmentioning
confidence: 97%
“…TQ-induced inflammation is mediated by the phosphoinositide 3-kinase (PI3K) and p38 pathways, while PEP-1-SIRT2-induced inflammation is mediated by the p38 and ERK pathways. The authors also reported that salinomycin (SAL) causes the dedifferentiation of rabbit articular chondrocytes via the ERK pathway, as determined by increased ERK activity without alterations in JNK and p38 activity following treatment with SAL 79 . Recently, the authors revealed that PEP-1-glutaredoxin-1 increased endoplasmic reticulum-stress and then stimulated the dedifferentiation of rabbit chondrocytes via the ERK-1/2 pathway 75 .…”
Section: Introductionmentioning
confidence: 97%
“…The observation of aggrecan fluorescent staining in cells isolated from rabbit knee cartilage indicates isolated chondrocyte activity ( Figure 5 E). Furthermore, Sox-9 played a crucial role in the specific activation of collagen type II, and was a key transcriptional regulator of chondrocyte differentiation, demonstrating it to be an important protein for chondrocyte expression [ 38 , 41 , 42 ]. Sox9 was observed by fluorescent staining, indicating chondrocyte expression, as shown in Figure 5 F.…”
Section: Resultsmentioning
confidence: 99%
“…The knee joint was a common sight of OA [6] , cartilage degeneration will affect the physiological function of chondrocytes [21] . The classical Wnt/β-catenin pathway regulates the bone metabolism and bone formation and the development and remodeling of cartilage tissue, which was related to OA [8,22] .…”
Section: Protein and Mrna Expression Of Wnt-1 β-Catenin And Gsk-3β In Chondrocytesmentioning
confidence: 99%
“…PRP can treat skeletal muscle injury [24] and release the growth factors involved in cartilage repair to promote cartilage regeneration [28] . Intra-articular injection of PRP can improve the International Knee Documentation Committee (IKDC) score of patients with knee cartilage degeneration [20] , while PRP can promote the proliferation of rabbit auricle chondrocytes in vitro [21] .…”
Section: Protein and Mrna Expression Of Wnt-1 β-Catenin And Gsk-3β In Chondrocytesmentioning
confidence: 99%